A Note on the Consequences of a Hot Mitochondrion: Some Recent Developments and Open Questions - Fahimi, Peyman; Nasr, Mohamed A.; Castanedo, Lazaro M. A.; Cheng, Youji; Toussi, Cyrus Ahmady; Matta, Cherif Farid (Biophysical Bulletin, 2020)
Background: Chrétien and co-workers (PLOS Biology. 2018;16(1):e2003992) recently suggested that the mitochondrion might possibly be hotter than its surrounding (by as much as 10°C).Objectives: To examine the validity of this claim and review the possible implications and repercussion of such a claim – if true – on some aspects of mitochondrial biochemistry and biophysics.Results: Both the chemical gradient and the electrical gradient Gibbs energy terms in the central equation of chemiosmotic theory are temperature dependent, the first explicitly and the second implicitly. A hotter mitochondrion – as claimed – would imply a 3% correction in the chemical gradient term, but we cannot estimate the corresponding effect on the electrical term at this time since the functional dependence of the voltage on the temperature is not known to the best of the authors’ knowledge. Further, if this claim is true and to the extent claimed (10°C), this may imply some heat-engine character for mitochondrial thermodynamic operation albeit this may only represent 4% at most.Conclusions: Doubts and criticisms regarding the suggestion of a hotter mitochondrion have been raised and are briefly discussed. These doubts are contrasted with some data and considerations that support the claim of a hotter mitochondrion. It is concluded that the mitochondrion is probably hotter than its environment but not to the extent claimed by Chrétien et al. and that the thermodynamic efficiency and the mode of operation of the mitochondrion as an electrochemical battery are very slightly perturbed by even the maximum claimed revision of the temperature of its operation.